Ischemia-reperfusion histopathology alterations of the rabbit intestinal wall with and without exclusion of the collateral mesenteric circulation supply - Gomes,Otoni Moreira (2010)
PURPOSE: To evaluate the histopathology alterations of the intestinal mucosa of rabbits submitted to different times of mesenteric artery ischemia and reperfusion with and without celiac artery collateral circulation supply. METHODS: Two groups of eight male New Zealand white rabbits (weight 2.2-3.5 kg) were used in this study. In the Group 1 animals, the proximal mesenteric artery was occluded for 60 min with an atraumatic vascular clamp, followed by reperfusion for 60 min. In the Group 2 animals the small bowel and mesentery were cut 30cm and 60cm far from the gastroduodenal pyloric transition before the proximal mesenteric artery occlusion. Small bowel biopsies were obtained before ischemia (control), after 30 min and 60 min of mesenteric ischemia and at 30 and 60 min. of mesenteric artery reperfusion. RESULTS: In the Group I animals, the followings histopathology grade results were observed: t1, mean 0.4 + 0.29; t2, mean 1.9 ± 0.38; t3, 1.9 ± 0.33; t4, 1.2 ± 0.36 and t5, 1.2 ± 0.32. Differences between t0 and t2 and between t3 and t4 were statistically significant (p<0.05). Differences between t2 and t3 and t4 and t5 were not significant (p>0.5). In the Group II animals, it was observed: t1, mean 1.6 ± 0.33; t2, 2.4 ± 0.36; t3, 3.0 ± 0.35; t4 3.4 ± 0.31; t5, 3 ± 031. Differences between t0 and t1, t1 and t2, and t2 and t3 were significant (p<0.05). Differences between histopathology grades results of samples t1 to t5 in Group 1 and 2 were statistically significant (p<0.5). CONCLUSION: Microscopic examination of the biopsies revealed significant evidence of worse small bowel wall ischemia-reperfusion lesions by exclusion of the celiac artery collateral circulation supply.